Development and validation of a rapid and simple UPLC/MS method for quantification of therapeutic and toxic valproic acid concentrations in patient plasma - Antunović, Marko; Djordjević, Snežana; Kilibarda, Vesna; Džudović, Jelena; Repić, Aleksandra; Bulat, Zorica (Archives of Pharmacy, 2022)
Valproic acid (VPA) is antiepileptic drug with a long history of clinical use, increasingly applied in the treatment of various diseases (bipolar disorder, migraine prophylaxis, etc). Due to significant inter-individual differences VPA concentration is often measured in the purpose of therapeutic drug monitoring (TDM). Acute poisonings with this drug represent a significant problem. According to the American Association of Poison Control Centers, there has been VPA poisoning incidence increase in the last 20 years. Reports from the National Poison Control Center in Belgrade list VPA as one of the three most common causes of antiepileptic drugs intoxications. This paper aimed to develop a modern analytical method for VPA quantification in patient plasma. UPLC/MS method with fast and simple sample preparation has been validated. After protein precipitation, VPA was extracted from 100 µL plasma using HLB cartridges. Caprylic acid solution was used as internal standard. Chromatographic separation was achieved on C18 column (1.8 µm, 2.1 X 150 mm) with gradient elution at constant mobile phase flow. Good peak resolution was achieved (RtVPA - 4.73 min, RtISTD - 4.94 min). Validation was performed according European Medicines Agency recommendations. Based on statistical analysism it was shown that the method is precise, accurate, specific, sensitive and linearity is confirmed in a wide range of concentrations (1-250 mg / L). Advantages of this method are simple preparation procedure from a small amount of sample, without prior derivatization and short duration of analysis, which fully satisfies the needs of TDM and urgent toxicological analyses.